THE EARLY DETECTION OF RESPIRATORY SYSTEM DISEASES BY USING THE CERTAINTY FACTOR METHOD - Siti Nuraisyah Suci Dewi Maharani Sianipar; Jeperson Hutahaean; Muthia Dewi (Informatika, Universitas Jenderal Soedirman, 2022)
Respiration or commonly referred to as breathing is the process of inhaling free air containing O2 (oxygen) and expelling air containing CO2 (carbon dioxide) as the rest of the oxidation out of the body. In detecting diseases of the respiratory system, it takes the role of a doctor as an expert in the field of health to detect it. To consult a doctor, one must come to the hospital and undergo a series of procedures, so that it takes time to queue and is not effective if the patient has to get treatment quickly. To overcome this problem, an expert system is needed that can be accessed easily, provides accurate, fast and accurate information on detection results and provides education on early treatment of disease detection results. The method used to detect respiratory system diseases is the certaity factor method. From the calculations that have been inputted by the patient, the results obtained are 93% confidence in Pneumonia. The application of an expert system with the Certaint Factor method in early detection of web-based respiratory system diseases based on the patient's symptom history provides convenience for patients and provides education about respiratory system diseases and how to treat them.